ION ALBULESCU ŞI HORAŢIU CATALANO, e-DIDACTICA. THE ONLINE TEACHING PROCESS. Bucharest, Didactica Publishing House, 2021, 416 pages, ISBN 978-606-048- 366-3 - Gina-Florentina TUDORACHE; Mihaela BADEA (National Centre for Policy and Evaluation in Education, 2021)
BOOK REVIEW